VALUE ENGINEERING FLY ASH OPTIMU ANALYSIS VALUE ENGINEERING FLY ASH OPTIMUM FOR MASS CONCRETE - Agus Komarudin; Helmy Darjanto; Rooslan Edy Santosa (LPPM of NAROTAMA UNIVERSITY, 2021)
Big budget for mass concrete raft foundation volume 24,603 m3, fc35 MPa, wctitious ratio 0,4, fly ash 15%, fresh concrete 320C, concrete using ice water. The purpose of this study, to find alternative concrete, by analyzing the Value Engineering analysis of the optimum fly ash, it is expected that the cost of concrete is more economical, with quality still achieved. The research was carried out with the research concept of comparing the above concrete with an alternative concrete optimum fly ash, with stage on stages of information, stages of functional analysis, stages of creative, evaluation stage, recommendation stage, implementation stage, the research alternative began on concrete designs, conducting experiments, analyzing fresh concrete, analyzing peak temperatures, analyzing strength and analyzing costs.The results of fly ash concrete 35%, compressive strength achieved fc 35 MPa, the cost was more efficient 12.69% than the initial cost of Rp. 24,233,955,000.00 Concrete fly ash 35% could be used as alternative. Regarding the application of value engineering, it is influenced by knowledge of value engineering and practices of it from decision holders and the absence of conflicts, of interest, of certain parties in the Indonesian construction industry.